2009
DOI: 10.1111/j.1399-0004.2009.01175.x
|View full text |Cite
|
Sign up to set email alerts
|

Plumbing in the embryo: developmental defects of the urinary tracts

Abstract: Kidney and urinary tract malformations are among the most frequent developmental defects identified in newborns. Ranging from asymptomatic to neonatal lethal, these malformations represent an important clinical challenge. Recent progress in understanding the developmental origin of urinary tract defects in the mouse and other animal models suggests a new framework for the interpretation of these defects in humans. Gene inactivation studies in mice provided invaluable information on the formation of the Wolffia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 77 publications
1
59
0
Order By: Relevance
“…Despite its simple design and the relevance of congenital defects of the ureteric wall, only a small number of genes crucial for development of the ureteric mesenchyme have been characterized in recent years (Airik and Kispert, 2007;Uetani and Bouchard, 2009). Phenotypic analyses of mutant mice suggested that the Tbox transcription factor gene 18 (Tbx18) specifies the ureteric mesenchyme (Airik et al, 2006); that Bmp4, a member of the family of secreted bone morphogenetic proteins, inhibits budding and branching morphogenesis of the distal ureteric epithelium, directs a ureteric fate and/or promotes SMC differentiation (Brenner-Anantharam et al, 2007;Dunn et al, 1997;Miyazaki et al, 2003); that the transcriptional regulators GATA binding protein 2 (Gata2), teashirt zinc finger family member 3 (Tshz3) and SRYbox containing gene 9 (Sox9) act as downstream mediators of Bmp4 function in the mesenchyme to activate expression of myocardin (Myocd), the key regulator of SMC differentiation Caubit et al, 2008;Wang and Olson, 2004;Zhou et al, 1998); and that sonic hedgehog (Shh) signaling from the ureteric epithelium maintains Bmp4 in the mesenchyme and dose-dependently inhibits SMC fates (Yu et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Despite its simple design and the relevance of congenital defects of the ureteric wall, only a small number of genes crucial for development of the ureteric mesenchyme have been characterized in recent years (Airik and Kispert, 2007;Uetani and Bouchard, 2009). Phenotypic analyses of mutant mice suggested that the Tbox transcription factor gene 18 (Tbx18) specifies the ureteric mesenchyme (Airik et al, 2006); that Bmp4, a member of the family of secreted bone morphogenetic proteins, inhibits budding and branching morphogenesis of the distal ureteric epithelium, directs a ureteric fate and/or promotes SMC differentiation (Brenner-Anantharam et al, 2007;Dunn et al, 1997;Miyazaki et al, 2003); that the transcriptional regulators GATA binding protein 2 (Gata2), teashirt zinc finger family member 3 (Tshz3) and SRYbox containing gene 9 (Sox9) act as downstream mediators of Bmp4 function in the mesenchyme to activate expression of myocardin (Myocd), the key regulator of SMC differentiation Caubit et al, 2008;Wang and Olson, 2004;Zhou et al, 1998); and that sonic hedgehog (Shh) signaling from the ureteric epithelium maintains Bmp4 in the mesenchyme and dose-dependently inhibits SMC fates (Yu et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The second major process is urogenital sinus (cloaca) development from endodermal cells, forming a definite urinary bladder, ureter-bladder connection and urethra (gene regulation, e.g. by Aldh1a2, PTPRF, PTPRS, NFIa, L1-CAM and others) [40][41][42] . The UT is also developmentally linked with the genitals, mostly through key Müllerian and Wolffian duct regulators [35] .…”
Section: Discussionmentioning
confidence: 99%
“…The correct rostral-caudal positioning of the UB is very important, as buds that form in the wrong position results in a ureter that fails to connect correctly to the bladder. 4 After the UB penetrates the metanephric mesenchyme (E11.0), it begins to branch repeatedly, mostly by bifurcation at the tips. 5 Other modes of branching (lateral budding and terminal trifurcation) also occur less frequently, at least in organ culture; 5 the patterns of branching that occur in vivo have not been well documented in the mouse kidney, as they have been in the lung.…”
Section: Introductionmentioning
confidence: 99%